The Application of Delon and McLean Method and End User Computing Satisfaction to Analyze User Satisfaction of Mobile Banking Applications - Dewi, Yoana Amelia; Imanirubiarko, Sabda; Simbolon, Dwi Maria; Tubagus, Munir; Nurdiani, Tanti Widia (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
The purpose of this study is to identify the variables that affect users' satisfaction with mobile banking apps. This study was carried out with a quantitative methodology. Users of mobile banking apps make up the study's demographic. Purposive sampling was used to choose 200 samples with active user criteria, ensuring that the participants in the study who answered the questionnaire were actual users of the mobile banking app. After that, analysis was done with Smart-PLS software and the PLS-SEM technique based on outer and inner models and demographics. It is possible to draw the conclusion that, in general, consumers are happy with the mobile banking application based on the discussion's outcomes. The variables content, accuracy, convenience of use, timeliness, system quality, information quality, and service quality that affect user satisfaction with the mobile banking application are the subject of seven recognized theories. One hypothesis is found to be false. This indicates that consumer happiness is unaffected by the variable. According to the study's findings, in order to keep users of the mobile banking app satisfied, it is imperative to maintain or enhance the system's quality, information quality, convenience of use, timeliness, content, and service quality.